INVESTASI AKHIRAT: MEMAKSIMALKAN POTENSI ZAKAT MAL UNTUK KESEJAHTERAAN UMAT - Rahmayani, Aiva; Ghoffar Ismail (Jurnal Ilmiah Ekonomi Islam, 2025)
This study aims to analyze the potential for optimizing zakat mal in improving the welfare of the people through the concept of “investment in the hereafter.” Zakat mal, as one of the pillars of Islamic economics, plays an important role in the distribution of wealth and economic empowerment of the community. However, its distribution has not yet reached its maximum potential in overcoming poverty and social inequality. This study employs a descriptive qualitative approach through a literature review of various primary and secondary sources related to zakat, community welfare, and the concept of investment from an Islamic perspective. Data collection methods include academic literature reviews, books, scientific journals, and official documents from zakat management institutions. Data analysis was conducted thematically, identifying key concepts, patterns, and relationships between variables to build a conceptual framework for afterlife investment through zakat mal. The research findings indicate that an afterlife investment approach in zakat mal management can transform zakat from mere consumption into sustainable productive capital. This concept emphasizes the distribution of zakat for programs that not only meet basic needs (consumptive) but also create economic independence (productive) for mustahik, such as skills training, business capital, or sustainable education programs. Optimizing zakat mal as an investment in the afterlife requires transparent, accountable, and innovative management strategies from zakat management institutions, as well as awareness among zakat payers of the long-term impact of their zakat. The implementation of this concept is expected to significantly improve the holistic and sustainable well-being of the community, in line with the objectives of Islamic sharia.